Frequencies of the Transferrin Alleles and Genotypes in West African Dwarf Goats of Southwestern Nigeria (2018)
The aim of this study was to determine the frequencies of Transferrin alleles and genotypes in West African Dwarf (WAD) goat. 140 adult WAD goats, maintained in four Southwestern States of Nigeria were used in the study. The polymorphism of transferrin was determined using Cellulose Acetate electrophoresis technique. It was found that the transferrin was controlled by two codominant alleles (TfA and TfB) in WAD goats. These two alleles, because of the codominant nature of inheritance, control the occurrence of three transferrin genotypes in the analyzed populations. The first two (TfAA and TfBB) were homozygous while the third one (TfAB) was heterozygous. The TfAB genotype was predominant with frequency of 0.90, 1.00, 0.87 and 0.55 in Ogun, Ondo, Osun and Oyo States respectively with a mean frequency of 0.83±0.20 while TfBB genotype was least common except for population from Osun State with a frequency of 0.05, 0.00, 0.22 and 0.15 in Ogun, Ondo, Osun and Oyo States respectively with a mean frequency of 0.08±0.07. The frequencies of transferrin alleles were 0.50, 0.50, 0.45 and 0.58 for TfA and 0.50, 0.50, 0.55and 0.43 for TfB in Ogun, Ondo, Osun and Oyo States respectively with a mean frequency of 0.49±0.05. Transferrin system showed genetic equilibrium in the analyzed population (χ2 value = 1.780). The observed heterozygosity was 0.91, 1.00, 0.87 and 0.55 43 in Ogun, Ondo, Osun and Oyo States respectively with a mean frequency of 0.84 and average Fis value of -0.6